2010
DOI: 10.1155/2010/593059
|View full text |Cite
|
Sign up to set email alerts
|

The Cost Efficiency of the Brazilian Electricity Distribution Utilities: A Comparison of Bayesian SFA and DEA Models

Abstract: The purpose of this study is to evaluate the efficiency indices for 60 Brazilian electricity distribution utilities. These scores are obtained by DEA (Data Envelopment Analysis) and Bayesian Stochastic Frontier Analysis models, two techniques that can reduce the information asymmetry and improve the regulator's skill to compare the performance of the utilities, a fundamental aspect in incentive regulation schemes. In addition, this paper also addresses the problem of identifying outliers and influential observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…Wang et al (2016) [15] reported that various DEA models and DEA-based modeling approaches such as CCR (Charnes-Cooper-Rodes); Undesirable Outputs, Malmquist, and Window have been recently applied in both private and public sectors across countries. For example, the CCR-DEA is applied to study the cost-effectiveness of electricity distribution facilities in Brazil [16] or performance-efficiency among Vietnamese steel manufacturers [17]. The studies applied to measure sustainability in supply chains with DEA techniques are very remarkable [18].…”
Section: Data Envelopment Analysis (Dea) Methodsmentioning
confidence: 99%
“…Wang et al (2016) [15] reported that various DEA models and DEA-based modeling approaches such as CCR (Charnes-Cooper-Rodes); Undesirable Outputs, Malmquist, and Window have been recently applied in both private and public sectors across countries. For example, the CCR-DEA is applied to study the cost-effectiveness of electricity distribution facilities in Brazil [16] or performance-efficiency among Vietnamese steel manufacturers [17]. The studies applied to measure sustainability in supply chains with DEA techniques are very remarkable [18].…”
Section: Data Envelopment Analysis (Dea) Methodsmentioning
confidence: 99%
“…According to Berg and Lin (2008), Castiglione et al (2018), another pitfall related to the application of the DEA method relies on the fact that this methodology does not consider random shocks that cannot be controlled by the producer, something that can be instead done through the application of the SFA. Further, the SFA has been preferred to non‐parametric approaches as the latter have been proven to perform poorly in the presence of outliers (Koop et al, 1999; Simar, 2003; Simar & Zelenyuk, 2011) while according to Pereira de Souza et al (2010) the SFA methodology is relatively more robust to the presence of outliers, given the assumptions about the distribution of its error term.…”
Section: Empirical Designmentioning
confidence: 99%
“…Researchers have dedicated their consideration regarding contrasting the parametric and non-parametric frontier methodologies utilizing information from non-financial firms. Pereira de Souza et al (2010) assess the efficiency of 60 Brazilian power and appropriation utilities by utilizing both DEA and Bayesian SFA models. They demonstrated that efficiency scores obtained from the SFA model are higher than the DEA; however, the (Pearson & Spearman) relationships between the DEA and SFA models are moderately high.…”
Section: Literature Reviewmentioning
confidence: 99%